2001
DOI: 10.1093/jn/131.9.2343
|View full text |Cite
|
Sign up to set email alerts
|

Selenium from Selenium-Rich Spirulina Is Less Bioavailable than Selenium from Sodium Selenite and Selenomethionine in Selenium-Deficient Rats

Abstract: The bioavailabilty of selenium (Se) from selenium-rich Spirulina (SeSp) was assessed in Se-deficient rats by measuring tissue Se accumulation and glutathione peroxidase (GSH-Px) activity. For 42 d, rats were subjected to dietary Se depletion by consumption of a Torula yeast (TY)-based diet with no Se; controls were fed the same diet supplemented with 75 microg Se/kg diet as sodium selenite. Se-deficient rats were then repleted with Se (75 microg/kg) by the addition of sodium selenite, selenomethionine (SeMet) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…Our results are consistent with those of Muller et al 34 who showed, in growing rabbits, that the selenium deficiency decreases the GPx activity in the plasma and the organs. Our results are also consistent with those of Cases et al, 35 who observed a decrease in the GPx activity of depleted rats. Wu et al 36 showed that a selenium depletion significantly decreased the GPx activity and the total antioxidant capacity in the rat arterial wall, the heart, the liver, and the kidney.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are consistent with those of Muller et al 34 who showed, in growing rabbits, that the selenium deficiency decreases the GPx activity in the plasma and the organs. Our results are also consistent with those of Cases et al, 35 who observed a decrease in the GPx activity of depleted rats. Wu et al 36 showed that a selenium depletion significantly decreased the GPx activity and the total antioxidant capacity in the rat arterial wall, the heart, the liver, and the kidney.…”
Section: Discussionsupporting
confidence: 94%
“…Torula yeast extract (Candida utilis; ICN) has been used in previous studies to establish selenium requirements for the production of the selenoenzyme nicotinic acid hydroxylase in Clostridium barkeri (16) as well as in the formulation of a mammalian diet demonstrated to cause selenium deficiency (5,39). An autolysate of torula yeast extract (ICN) was generated by incubating yeast (250 g/liter in distilled water) at 50°C overnight, followed by clarification by centrifugation at 20,000 ϫ g for 1 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Analyses of the elemental contents of microalgae (Quigg et al 2011) and macroalgae (Tuzen et al 2009; Pereira 2011) rarely include Se, even though it is present in both (Fournier et al 2005). Se readily bioaccumulates in algae (Cases et al 2001; Fournier et al 2005), and Se-deficiency in rats can be alleviated by oral supplementation with Se-rich Arthrospira (spirulina), as indicated by increased activity of (Se-containing) glutathione peroxidase in the kidneys and liver (Cases et al 2001). However, increases in this enzyme activity were greater in rats supplied selenite or selenomethionine (more reactive species) than with the same dosage of Se-rich cyanobacterium, likely due to lower bioavailability of the cyanobacterial Se.…”
Section: Antioxidantsmentioning
confidence: 99%